“Pay for Success” Projects: Financing Interventions That Address Social Determinants of Health in 20 Countries - Iovan, Samantha (Am J Public Health, 2018)
Over the past eight years, there has been an increase in the use of pay for success (PFS) as a financing tool whereby private investors provide initial funding for preventive health and human service interventions. If an independent evaluator deems the interventions successful, investors are repaid by the government. To better understand how PFS is used, we created a global landscape surveillance system to track and analyze data on all PFS projects that have launched through 2017. We focus on the potential for PFS to improve population health by funding interventions that target the social determinants of health. Our findings show that all launched projects to date have implemented interventions aimed at improving the structural and intermediary social determinants of health, primarily in socioeconomically disadvantaged populations. Although there are some challenges associated with PFS, we believe it is a promising tool for financing interventions aimed at social determinants of health in underserved and marginalized populations.